HUBUNGAN PENERAPAN KOMUNIKASI TERAPEUTIK OLEH PERAWAT DENGAN KEPUASAN PASIEN DI INSTALASI GAWAT DARURAT - Miming Oxyandi (Jurnal Kesehatan : Jurnal Ilmiah Multi Sciences, 2019)
Background: Therapeutic communication is a shared experience between nurse-clients that aims to resolve client problems. Therapeutic communication includes interpersonal communication with a starting point for mutual understanding between nurses and patients. The fundamental problem of this communication is mutual need between nurses and patients, so that it can be categorized into personal communication between nurses and patients, where nurses help and Clients receive assistance. Objective: this study aims to determine the relationship between the application of therapeutic communication by nurses and patient satisfaction in the Emergency Room (IGD) Institute of Muhammadiyah Hospital Palembang. Method: this study used a cross sectional design. The research sample consisted of 32 respondents (16 nurse respondents and 16 patient respondents) were taken using incidental sampling techniques for patient respondents while those perwat respondents used a total sampling technique. Results: the study showed no relationship between the application of communication (p-value 0.213), orientation phase (p-value 0.213), work phase (p-value 0.213), termination phase (p-value 1.00). Suggestion: for hospitals to improve the application of more optimal therapeutic communication to patients, especially in the emergency room.